Predictive failure? Intelligence-gathering and the FLQ - St. Clair, Ronald Benjamin (University of Ottawa (Canada), 2005)
It has been the Canadian federal government's consistent position that the decision to invoke the War Measures Act had been arrived at due to a lack of available intelligence on the FLQ. They contend that sufficient advance warning of the FLQ's intentions to kidnap political officials before the October Crisis of 1970 had not been provided, and they were not given adequate intelligence on the nature and capabilities of the threat during the crisis. Essentially, the argument asserts that there had been a failure on the part of the intelligence-community in Canada to predict the FLQ's future actions. This thesis challenges the assumption of predictive failure through a critical analysis of the available primary source material on the subject. The analysis is accomplished in part by drawing upon the classical works in intelligence-gathering in order to identify the problems that have historically hampered intelligence-gathering efforts and to determine whether or not they were evident in the present case. Ultimately, this model of analysis contradicts the assumption of predictive failure by demonstrating that serious problems of intelligence-gathering had existed long before the October Crisis began. These problems compounded over time to ensure that, although adequate intelligence on the FLQ did exist, it's transmission from intelligence-gatherers to decision-makers was severely hampered.
Keywords: History, Canadian.; Political Science, General.